Promotion of order Bunyavirales to class Bunyaviricetes to accommodate a rapidly increasing number of related polyploviricotine viruses - Kuhn, Jens H; Brown, Katherine; Adkins, Scott; de la Torre, Juan Carlos; Digiaro, Michele; Ergünay, Koray; Firth, Andrew E; Hughes, Holly R; Junglen, Sandra; Lambert, Amy J; Maes, Piet; Marklewitz, Marco; et al. (Journal of virology, 2024)
Prior to 2017, the family included five genera of arthropod and rodent viruses with tri-segmented negative-sense RNA genomes related to the Bunyamwera virus. In 2017, the International Committee on Taxonomy of Viruses (ICTV) promoted the family to order and subsequently greatly expanded its composition by adding multiple families for non-segmented to polysegmented viruses of animals, fungi, plants, and protists. The continued and accelerated discovery of bunyavirals highlighted that an order would not suffice to depict the evolutionary relationships of these viruses. Thus, in April 2024, the order was promoted to class . This class currently includes two major orders, ( , , , , , , and ) and ( , , , , , , , and ), for hundreds of viruses, many of which are pathogenic for humans and other animals, plants, and fungi.